Finite element analysis of steel fibre reinforced concrete beam - Huong, Liong Yew, 1992- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2017